Barriers in EFL online learning experienced by learners during Covid-19 outbreak - Vivi Aulia (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
This research aimed at reviewing the barriers in EFL online learning experienced by learners in some countries like Indonesia, Saudi Arabian, Algeria, Jordan, and Ecuador during online learning gained from the research articles. This research was described descriptively with qualitative approach. The data being investigated in this research were five research articles from different researchers in different countries where they conducted research about barriers of EFL online learning during Covid-10 outbreak viewed from learners’ experiences. The results of this research showed that those five countries faced similar barriers in EFL online learning during Covid-19 outbreak. They were technical matter (internet connectivity) and social matter (passive interaction among teachers and learners). The conclusion stated that possible infrastructure for supporting high speed access internet should be considered by the policymakers in each country providing both technical and economic support to access it easily. Thus, for those who have barriers related to social matter, it was important for EFL teachers to create a strategy that made the class interactive and interesting as well as motivated the EFL learners interested to learn. Internal motivation from the EFL learners and teachers themselves to accommodate online learning creatively was needed.